Effects of Chlortetracycline Rumen-Protected Granules on Rumen Microorganisms and Its Diarrhea Therapeutic Effect - Yu, Yang; Li, Xin; Liu, Ziyao; Xu, Ying; Shen, Yue; Li, Guoji; Huang, Xianhui (Frontiers in Veterinary Science, 2022)
Chlortetracycline is a broad-spectrum antibiotic used as an oral medication in ruminants. However, this antibiotic affects the rumen microbial population, thereby upsetting the normal microbiota of ruminants. This study determined whether our newly developed chlortetracycline rumen-protected granules are relatively harmless to rumen microorganisms while effective against lamb E. coli diarrhea. We used a qPCR assay to quantify selected rumen microorganisms from lambs treated with or without oral chlortetracycline. We also assessed bacterial diversity in the rumen by 16S rRNA gene sequencing. Lambs were divided into three groups: one group given with oral chlortetracycline granules for seven days; one group with chlortetracycline premix; and one without treatment. Rumen fluid was collected on 0 d, 7 d, and 14 d of the experiment. In the therapeutic effect trial, cases of naturally E. coli-infected lamb with diarrhea were selected and divided into low, medium, and high dose groups of granules, premix, infection control, and healthy control groups. Treatments were continuously administered for seven days, and animals were observed for 14 days after drug withdrawal to score and evaluate the treatment effect. Results of qPCR and 16S rRNA gene sequencing showed that the granules could diminish the impact of chlortetracycline on rumen microorganisms compared with the premix. The diarrhea therapeutic effect trial showed that the oral administration of the chlortetracycline rumen-protected granules at the dose of 30 mg/kg·bw/d for seven days could effectively treat lamb diarrhea caused by E. coli. In conclusion, we provide a new drug preparation of chlortetracycline that can diminish the effect on the rumen microbiota while treating diarrhea caused by E. coli.